Efektivitas Program Self-Care Berbasis Sekolah terhadap Peningkatan Motivasi dan Perilaku Pencegahan Dini Hipertensi pada Remaja - Salami Salami; Fatiah Handayani (Universitas Faletehan, 2026)
Unhealthy lifestyles among adolescents contribute to the increasing prevalence of hypertension within this age group. One important prevention strategy is the implementation of a self-care program to enable adolescents to independently manage healthy lifestyles. This study aimed to examine the effectiveness of a school-based self-care program in improving motivation and early preventive behaviors toward hypertension among adolescents. This study employed a quasi-experimental design using a one-group pre-test and post-test approach, involving 120 students selected through accidental sampling. The intervention was delivered in the form of health education using PowerPoint presentations and leaflets. The research instrument was developed based on the CERDIK guidelines (regular health checks, eliminating cigarette smoke, physically active, having a balanced diet, getting enough rest, and managing stress) from the Health Ministry of Indonesia, which had been modified and tested for its validity and reliability. Data analysis was conducted using the Wilcoxon test to assess the effectiveness of the self-care management program. The results showed an improvement in the mean scores of adolescents’ motivation and behavior after receiving health education, with an increase of 13.5 in motivation scores and 1.8 in behavior scores. The Wilcoxon test indicated a significance value of 0.000 (p < 0.05), suggesting that the self-care education program was effective in improving students’ motivation and behaviors in preventing hypertension and has the potential to serve as a sustainable health promotion model.